Nutritional status of Hill Korwa preschool children of Jashpur:A particularly vulnerable tribal group of Chhattisgarh - Subal Das; Manisha Ghritlahre; Aafreen Siddiqui; Khangembam Somibabu Meitei (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Malnutrition is considered as one of the major public health problems in developing counties like India. AIMS: To understand the nutritional status of preschool children of Hill Korwa Tribe of Jashpur district, Chhattisgarh, India. MATERIALS AND METHODS: A crosssectional study was carried out among the preschool children of Hill Korwa Tribe, Jashpur district Chhattisgarh, India. In total, 106 children between 2-6 years of age including 60 boys and 45 girls were screened for their nutritional status and hygienic practices. Data of age and hygienic practice (lavatory use and drinking water) were collected from their parents/care takers and also from aanganwadi workers. The statistical analysis was done using statistical package with Statistical Package for Social Sciences (SPSS) Statistics version 23. Verbal approval from their parents was obtained before the beginning of data collection. RESULTS: The age-sex combined overall prevalence of undernutrition of the studied population is 54.7%. Comparatively girls are more undernourished (62.2%) than boys (49.2%). Negative significant sex difference (t = -2.967, sig = 0.010) in mean BMI at the age of 2 years has been observed. The highest prevalence of undernutrition was found among those children who are practicing open defecation (63.4%) than those children who were using toilets (36.9%). Significant age difference in the prevalence of nutritional status has been observed among girls (χ2 = 32.162, df = 8, P = 0.000). CONCLUSION: The present study reveals a high prevalence of undernutrition among Hill Korwa children aged between 2-6 years. Proper nutritional and awareness program on hygienic practices can have a significant impact in reduction of undernutrition among them. Target oriented and community specific program based on, survey report of health and nutritional status should be designed.